THE CONCEPT OF PROFESSIONAL COMPETENCE IN HIGHER EDUCATION AND THE STATE OF ITS FORMATION AMONG STUDENTS OF THE NATURAL SCIENCE FACULTY (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2021)
This article gives an explanation of the important role of the formation of professional competence in teaching English to students of the Faculty of Natural Sciences. Also, the concept of competence and professional competence in the higher education system is clarified. Like all faculties today, it is important for students of the Faculty of Natural Sciences to study English in accordance with their specialization. Considering this issue, several examples are provided related to this article. In this presented article the opinions and views of pedagogues and scientists all over the world are partially used.